Augmented Reality Applications in Teaching and Learning for topic of Current and Voltage Division for Technical and Vocational Education - Shed Sazly, Syed Zuhairy; Jambari, Hanifah; Noh@Seth, Nur Hazirah; Pairan, Mohamad Rasidi; Mohd Ahyan, Nurul Aini; Abdul Hamid, Mohd Zolkifli; Osman, Sharifah (Journal of Technical Education and Training, 2021)
The combination of technology Augmented Reality (AR) with educational content aims to create new ideas that can improve the effectiveness and attractiveness of teaching and learning for students in real-life scenarios. The use of AR technology can make the process of teaching and learning more enjoyable, in which students’ interest in learning can be stimulated. The AR technology has three characteristics. The first feature is that AR technology is a combination of virtual objects with the real world. The second feature is that AR operates in real time and interactively. The last feature is that it has 3 dimensions (3D) for virtual objects. In this study, the ADDIE model includes five phases, namely Analysis, Design, Development, Implementation and Evaluation, which are utilised to develop applications based on AR technology in education for the topic of Current and Voltage Division. To identify the effectiveness of the application of AR technology, a survey using questionnaire was conducted among pre-service teachers to know their perceptions of the development of AR applications namely as Voltrent AR. As this is a quantitative study where questionnaires were distributed to 73 students from the class of Bachelor of Technology with Education (Electric and Electronics) with Honours and Bachelor of Technology with Education (Living Skills) with Honours at Universiti Teknologi Malaysia (UTM) Skudai, Johor. Most respondents gave very positive feedback on the use of AR in education, especially for the topic of Current and Voltage Division. AR is viewed as a medium of instruction that is innovative, interesting and effective. Voltrent AR application development is successfully developed based on the ADDIE model, and the application development of the constructivism theory was applied in this AR application. Thus, the AR application development has reached the desired objective of producing application-based Augmented Reality as a teaching aid.